Hajuda - Azevedo, M. (Open Schools Journal for Open Science, 2020)
A recent study by the National Institute of Statistics (INE) reveals that almost half of the Portuguese population will be over 65 within the next 60 years. Also, about 40% of this population is alone for 8 hours or more per day. Almost one million elderly people are in solitude or isolation. How can we promote the return of the population over 65 to active life? How can we help caregivers to provide care for their loved ones with the knowledge we acquire in class? A society was born: Hajuda (Help in English). The main goal is to help those who need it most. Whether they are in bed or in solitude and social isolation. The results have been very promising.